ANALISIS FAKTOR-FAKTOR YANG MENINGKATKAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Pada Perusahaan Sektor Infrastruktur, Utilitas & Transportasi yang Terdaftar di BEI Periode 2012-2016) - Luqiana, Lulu; Cahyaningsih, Cahyaningsih; Zultilisna, Djusnimar (Jurnal Akrab Juara, 2018)
The purpose of this study is to analyze the influence of profitability, company size, the structure of public ownership, and the audit opinion to the timeliness of financial reports. The population in this study is the companies sectors infrastructure, utilities and transportation are listed on the Indonesian Stock Exchange period 2012 to 2016. The sampling method on this research is purposive sampling and obtained 36 companies. Data analysis method in this research is the logistic regression analysis. Results showed that Simultaneously, profitability, firm size, public ownership structure and the audit opinion have a significant influence on the timeliness of financial reports. Partially, Profitability and public ownership structure have a negative but not significant effect on timeliness of financial reports. Firm size and audit opinion have a positive and significant effect on the timeliness of financial reports. Keywords: Profitability, Firm Size, Public Ownership Structure, Audit Opinion, Timeliness